Transposon activation is a major driver in the genome evolution of cultivated olive trees (Olea europaea L.). Issue 1 (27th March 2020) - Jiménez‐Ruiz, Jaime; Ramírez‐Tejero, Jorge A.; Fernández‐Pozo, Noé; Leyva‐Pérez, María de la O; Yan, Haidong; Rosa, Raúl de la; Belaj, Angjelina; Montes, Eva; Rodríguez‐Ariza, Mª Oliva; Navarro, Francisco; Barroso, Juan Bautista; Beuzón, Carmen R.; et al.
Abstract: The primary domestication of olive ( Olea europaea L.) in the Levant dates back to the Neolithic period, around 6, 000–5, 500 BC, as some archeological remains attest. Cultivated olive trees are reproduced clonally, with sexual crosses being the sporadic events that drive the development of new varieties. In order to determine the genomic changes which have occurred in a modern olive cultivar, the genome of the Picual cultivar, one of the most popular olive varieties, was sequenced. Additional 40 cultivated and 10 wild accessions were re‐sequenced to elucidate the evolution of the olive genome during the domestication process. It was found that the genome of the 'Picual' cultivar contains 79, 667 gene models, of which 78, 079 were protein‐coding genes and 1, 588 were tRNA. Population analyses support two independent events in olive domestication, including an early possible genetic bottleneck. Despite genetic bottlenecks, cultivated accessions showed a high genetic diversity driven by the activation of transposable elements (TE). A high TE gene expression was observed in presently cultivated olives, which suggests a current activity of TEs in domesticated olives. Several TEs families were expanded in the last 5, 000 or 6, 000 years and produced insertions near genes that may have been involved in selected traits during domestication as reproduction, photosynthesis, seed development, and oil production. Therefore, a great genetic variability has been found in cultivated olive as a result of a significant activation of TEs during the domestication process.